KAJIAN KARAKTER PEMBENTUK LANSKAP BUDAYA MASYARAKAT ADAT KAJANG DI SULAWESI SELATAN - Rezky Nur Awalia; . Nurhayati; . Kaswanto (Jurnal Lanskap Indonesia, 2017)
Kajang is one of the indigenous communities in the Province of South Sulawesi. Kajang cultural landscape formed as a result of interaction between Kajang comunity and their environment. The problems which occurred in this cultural landscape is the degradation of cultural value. The problem caused by the carelessness of youth Kajang about their cultural heritage. The purpose of this study is to identify the landscape elements that formed the landscape character. The method of study was Landscape Character Assessment. The identification of landscape character refered to 11 elements of landscape according to McClelland et al. (1999). Based on the analysis result, the character of Kajang cultural landscape is traditional settlement with the tripatri zoning which depend on local natural resources (forest and agriculture) with the patuntung as their reliance. Landscape unit that shown strong character are sacred settlement area, sacred forest, and the elements around the settlement area such as ancestors tombs, batu temu gelang, balla tammua, and public well.